Characterization of the functional effects of ferredoxin 1 as a cuproptosis biomarker in cancer - Li, Xiang; Dai, Zihan; Liu, Jincheng; Sun, Zhenqian; Li, Na; Jiao, Guangjun; Cao, Hongxin (Frontiers in Genetics, 2022)
Background: Cuproptosis is a recently discovered form of programmed cell death. Ferredoxin 1 (FDX1) is a key gene that mediates this process. However, the role of FDX1 in human tumors is not clear. Methods: We comprehensively analyzed the differential expression and genetic alterations of FDX1 using multiomics data from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) database. Subsequently, we explored the association between FDX1 and tumor parameters such as genomic instability, RNA methylation modifications, immune infiltration and pathway activity. In addition, we performed functional enrichment analysis and assessed the sensitivity potential of FDX1-related drugs. Finally, we experimentally verified the dual functional effects of FDX1. Results: The analysis revealed differential expression of FDX1 in a variety of tumors. By analyzing the association of FDX1 expression with genomic instability, we identified a dual functional effect of FDX1. Further analysis demonstrated the generality of this pattern. Functional enrichment analysis revealed that FDX1 and its related genes play a role in human disease through biological pathways associated with cuproptosis. And we identified several potential drugs targeting FDX1. At last, the results of the experiments demonstrated the dual role of FDX1 in tumor proliferation. Conclusions: Our study reveals the dual functional effects of FDX1 in tumors and deepens the understanding of the effects of FDX1. In addition, it provides information for the development of cuproptosis-related drugs.